ROI in marketing : the design thinking approach to measure, prove, and improve the value of marketing - Phillips, Jack J., 1945-; Fu, Frank Q.; Phillips, Patricia Pulliam; Yi, Hong (President of Sinotrac) (McGraw-Hill, 2021)
"Discover a unique, proven methodology to measure, improve and demonstrate the value of your marketing campaigns and initiatives Understanding and serving your customers' needs is what marketing is all about, but how do you know your events, campaigns and communication initiatives are working at top efficiency and effectiveness? To ensure projects are aligned to business objectives, marketing professionals need a credible, proven evaluation process to measure impact and calculate your return on investment. In ROI in Marketing, the team at ROI Institute reveals their proven, unique ROI Methodology to do just that. Using their data-driven three-part process, you'll learn how to understand the customer better, so you can focus on the critical components of the customer decision-making process. Learn how to analyze and learn from any past failures, and how to adjust and improve the value-including the financial ROI-of current and future marketing campaigns and initiatives"--